Internationalization of PY: in-depth analysis of Australia and LR on international entry mode selection - Mota, Ana Rita Correia (2022)
PY is a Portuguese SME operating in the maritime industry delivering ship parts and equipment as well as services. As the basis for decision-making, an analysis of five potential countries was carried out using both macro and industry-specific factors. Finally, a marketing plan and financial forecasts for the project were conducted and adapted to Singapore, the country chosen as the best target. The present information complements the report with a literature review on the topic of international market selection for the maritime industry and an in-depth analysis of Australia, one of the potential target countries, considering various distinctive dimensions